2004
DOI: 10.3358/shokueishi.45.44
|View full text |Cite
|
Sign up to set email alerts
|

Production of Acrylamide in Agricultural Products by Cooking

Abstract: Some model studies were performed using various agricultural Products, to clarify the relation between cooking conditions and production of acrylamide (AA). Disc chips made from dried mashed potato, corn meal, wheat flour, rice flour (jyohshin-ko) and glutinous rice flour (shiratama-ko), and dried sesame (arai-goma) and dried almond were baked at 120ῌ200 for 5ῌ20 min, and the samples were analyzed for the levels of AA. When the samples were baked for 10 min, the highest production of AA was observed at 180ῌ200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…Acrylamide intake was also estimated from the amount of food and beverage intake and the acrylamide content database. The database was developed from published reports of measurements of common Japanese foods . In addition to heated processed foods such as bread, biscuit and cookies, or coffee, we considered the influence of home cooking such as stir‐fried vegetables, toast, or fried batter, to estimate the dietary acrylamide more accurately .…”
Section: Methodsmentioning
confidence: 99%
“…Acrylamide intake was also estimated from the amount of food and beverage intake and the acrylamide content database. The database was developed from published reports of measurements of common Japanese foods . In addition to heated processed foods such as bread, biscuit and cookies, or coffee, we considered the influence of home cooking such as stir‐fried vegetables, toast, or fried batter, to estimate the dietary acrylamide more accurately .…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the results suggested that frying vegetables would induce the formation of acrylamide. Its formation may be affected by many factors such as the presence of asparagines and reducing sugars in the vegetables, and the frying temperature and time (Takatsuki et al 2004;FAO/WHO 2011).…”
Section: Food Additives and Contaminants: Part A 801mentioning
confidence: 99%
“…Potato crisps, French fries, biscuits, crisp bread and crackers were reported to contain acrylamide in significant levels (up to the "mg kg −1 " level) in many countries (FAO/WHO 2011). Vegetables other than potatoes cooked in high temperature such as baking, grilling, roasting and pan-frying were also reported to contain acrylamide (up to the "μg kg −1 " level) in some overseas surveys and researches (Takatsuki et al 2004;Şenyuva & Gökmen 2005;FAO/WHO 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Acrylamide was not found in microwaved or boiled vegetables. Takatsuki et al (2004) Potatoes Processing parameters on acrylamide formation…”
Section: Amrein Et Al (2003)mentioning
confidence: 99%